Communicating sustainability through the adoption of the SDGs: evidence from the reporting systems of European companies - Carmo, Cecília M.R. (2024)
The adoption of the Sustainable Development Goals (SDGs) is increasingly becoming an integral part of sustainability reporting and used as a tool to disclose information on companies’ sustainability actions. In this context, the aim of this work is to investigate how the adoption of the SDGs has evolved in Europe, to extend previous evidence that does not go beyond the year 2018. For this purpose, a sample of European companies belonging to the Euro Stoxx 50 Index and the period from 2017 to 2021 were selected. Data was collected and processed using manual content analysis methods. The results show a clear tendency for European companies to adopt an increasing number of SDGs over the period analyzed. It was also observed that among the most adopted SDGs are: in the economic area, SDG 12 and SDG 8; in the social area, SDG 3, SDG 4 and SDG 5; and in the environmental area, the most adopted is the SDG 13.